Pengaruh Sunset Policy, Tax Amnesty dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak (Studi Kasus Pada Wajib Pajak Orang Pribadi Yang Terdaftar di KPP Pratama Serpong, Kota Tangerang Selatan) - Situmorang, Rosanti Putri; Septiani, Dwi (Universitas Katolik Soegijapranata, Semarang, 2025)
The purpose of this study is to determine the effect of sunset policy, tax amnesty and tax sanctions on taxpayer compliance (case study on individual taxpayers registered at KPP Pratama Serpong, South Tangerang) both partially and simultaneously. The type of method used in this study is quantitative method. The type of data used is primary data. The data analysis method used is multiple linear regression analysis and the data analysis techniques used are descriptive analysis techniques in the form of data quality tests, classical assumption tests and hypothesis tests. The results of this study show that partial sunset policy has a positive effect on taxpayer compliance, for tax amnesty partially affects taxpayer compliance, for tax sanctions partially affects taxpayer compliance. Meanwhile, simultaneously sunset policy, tax amnesty and tax sanctions affect taxpayer compliance.